ANALISIS KEKERINGAN LAHAN PERTANIAN+ BERBASIS PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS KABUPATEN BATANG HARI - Gema Anugrah; Dedi Hermon (JURNAL BUANA, 2026)
Batang Hari Regency is one of the districts most vulnerable to the dry season. This has an impact on the agricultural sector, which is a source of livelihood for most residents in the Batang Hari Regency area. According to BNPB inaRISK (2018), Batang Hari Regency is one of the provinces with a high drought threat with a score of 24.0 in the high-class category. This research aims to determine the distribution of areas at risk of drought on agricultural land in Batang Hari Regency by utilizing remote sensing data which is integrated with the physiographical conditions of the area that affect drought, which is then grouped into three classes of drought levels, namely: low, medium, and high. The data needed in this study include Normalized Different Vegetation Index (NDVI) map, Land Surface Temperature (LST) map, rainfall average map, hydrogeological map, and soil type map.From the data processing, it is found that the area with a low agricultural drought level is 55382.60 hectares with a total percentage of 26.73%, moderate drought level is 121303.16 hectares with a total rate of 58.56%, and high drought level is 30472.74 hectares with a total percentage of 14.71% of the agricultural area.